1992
DOI: 10.1017/s0269964800002692
|View full text |Cite
|
Sign up to set email alerts
|

On the Assignment of Customers to Parallel Queues

Abstract: This paper considers routing to parallel queues in which each queue has its own single server and service times are exponential with nonidentical parameters. We give conditions on the cost function such that the optimal policy assigns customers to a faster queue when that server has a shorter queue. The queues may have finite buffers, and the arrival process can be controlled and can depend on the state and routing policy. Hence our results on the structure of the optimal policy are also true when the assignin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 23 publications
2
47
0
1
Order By: Relevance
“…Observe that in the current model there is no equation relating states like i + ej and i, like in the standard routing model with one server for each queue (e.g., Eq. (4.4) in Hordijk and Koole [4]). We do not need such an equation here: the total number of functioning components remains stochastically the same under each policy, due to the structure of the model and the fact that idleness is not allowed (unless all components are functioning).…”
Section: Warm Stand-by Modelmentioning
confidence: 93%
“…Observe that in the current model there is no equation relating states like i + ej and i, like in the standard routing model with one server for each queue (e.g., Eq. (4.4) in Hordijk and Koole [4]). We do not need such an equation here: the total number of functioning components remains stochastically the same under each policy, due to the structure of the model and the fact that idleness is not allowed (unless all components are functioning).…”
Section: Warm Stand-by Modelmentioning
confidence: 93%
“…Since an incoming customer can only be rejected if all the buffers are busy, a systemwide efficient routing policy is one that maximizes the expected number of customers served over an unbounded horizon. Hordijk and Koole [4] have shown that any systemwide efficient policy has the following structure: an arriving customer should be assigned to a faster server when that server has a shorter queue. They refer to this type of policy as the "Shorter Queue Faster Server Policy, SQFSP."…”
Section: Efficiencymentioning
confidence: 99%
“…They refer to this type of policy as the "Shorter Queue Faster Server Policy, SQFSP." As it is pointed out in [4], this characterization is incomplete in general but sufficient whenever the servers have identical service-time distributions. In this case, the optimal policy follows a simple "Shortest Queue" rule, incoming customers should be routed to the shortest queue.…”
Section: Efficiencymentioning
confidence: 99%
“…Since then the optimality of JSQ has been shown in many other similar settings, e.g., Weber (1978) considered arbitrary arrivals together with service times having a non-decreasing failure rate, while Johri (1989) considered state-dependent exponential service times, having a multi-server queues as a special case. Hordijk and Koole (1992) considered non-identical exponential servers and showed that jobs should always…”
Section: Introductionmentioning
confidence: 99%